Creatine kinase and its relationship with match performance in elite Australian Rules football - Hunkin, S. L.; Fahrner, B.; Gastin,. P. B. (Journal of Science and Medicine in Sport, 2014)
Objectives: The purpose of this study was to examine the relationships of pre-match creatine kinase on match performance measures in elite Australian Rules football. Design: Repeated measures single cohort longitudinal. Methods: Twenty-nine elite Australian Rules football players were assessed across a competitive season. Creatine kinase was collected 24-36 h pre-match, and investigated against two measures of match performance; performance ranking scores (based on playing statistics) and coach's performance ratings. Multi-level modelling was applied and player characteristics were considered as moderating variables in the analysis. Results: Average player pre-match creatine kinase was 485% greater than baseline values. Six-minute running performance was negatively related with average player pre-match creatine kinase (r = -0.432, p = 0.019). Creatine kinase was negatively associated with performance ranking scores (r = -0.149, p = 0.035), although increases in playing experience reversed this relationship (p = 0.003). Coach's subjective ratings declined with elevations in pre-match creatine kinase (p = 0.002). Conclusions: Increases in creatine kinase from baseline to pre-match indicate residual muscle damage. Small decrements in match performance were explained by increases in pre-match creatine kinase. However, player characteristics related to age and experience appear to be important moderating variables. Elevated pre-match creatine kinase likely represents a state of incomplete recovery from the preceding week, and over time, residual muscle damage. Creatine kinase monitoring may be most appropriately used with young and inexperienced players, and those with lower aerobic running performance to assist in the modulation of training and recovery loads to optimise match preparation and performance.